2017
DOI: 10.1007/s00403-017-1794-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the DLQI appropriate for medical decision-making in psoriasis patients?

Abstract: Dermatology Life Quality Index (DLQI) is the most commonly applied measure of health-related quality of life (HRQoL) in psoriasis patients. It is among defining criteria of moderate-to-severe psoriasis and present in treatment guidelines. Our objective was to estimate preference-based HRQoL values (i.e., utilities) for hypothetical health states described by the 10 items of the DLQI in psoriasis patients. Moreover, we compare results to findings of a similar study previously conducted among the general public.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
0
19
0
10
Order By: Relevance
“…The preponderance of evidence supports its validity, reliability and responsiveness in psoriasis . However, there exists a growing body of literature questioning key aspects of its validity including the lack of unidimensionality; differential item functioning; failure to capture the psychological burden of disease; scores being affected by transcultural variability; the lack of ability to assess individual HRQoL impact in terms of an individual's personal lifestyle, values and experiences (compared with the Patient‐Generated Index) and discrepancies identified between DLQI scores and health utility values …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preponderance of evidence supports its validity, reliability and responsiveness in psoriasis . However, there exists a growing body of literature questioning key aspects of its validity including the lack of unidimensionality; differential item functioning; failure to capture the psychological burden of disease; scores being affected by transcultural variability; the lack of ability to assess individual HRQoL impact in terms of an individual's personal lifestyle, values and experiences (compared with the Patient‐Generated Index) and discrepancies identified between DLQI scores and health utility values …”
Section: Discussionmentioning
confidence: 99%
“…2,20 However, there exists a growing body of literature questioning key aspects of its validity including the lack of unidimensionality; 21 differential item functioning; [21][22][23][24] failure to capture the psychological burden of disease; 25 scores being affected by transcultural variability; [25][26][27] the lack of ability to assess individual HRQoL impact in terms of an individual's personal lifestyle, values and experiences (compared with the Patient-Generated Index) 28 and discrepancies identified between DLQI scores and health utility values. 29,30 As a part of this proposal, we evaluated the construct validity of DLQI-R. In terms of correlations with other core outcome measures, such as PASI, EQ-5D-3L and EQ-VAS, the DLQI-R performed better than the original DLQI.…”
Section: Discussionmentioning
confidence: 99%
“…that all items in the scale underlie the same construct) and detected that certain DLQI items are affected by external factors, such as age, gender and cultural background of patients . Another study found discrepancies between DLQI scores and time trade‐off utility values, suggesting that HRQoL in two patients with identical DLQI scores might be significantly different, while patients whose DLQI scores differ larger than the minimal clinically important difference may be equal . Considering the number of jurisdictions, in which the DLQI is used in national guidelines, including the European S3‐Guidelines on the systemic treatment of psoriasis vulgaris, the amount of patients affected worldwide may be very large.…”
Section: Discussionmentioning
confidence: 99%
“…16,20,34,[55][56][57][58][59] Another study found discrepancies between DLQI scores and time trade-off utility values, suggesting that HRQoL in two patients with identical DLQI scores might be significantly different, while patients whose DLQI scores differ larger than the minimal clinically important difference may be equal. 60,61 Considering the number of jurisdictions, in which the DLQI is used in national guidelines, including the European S3-Guidelines on the systemic treatment of psoriasis vulgaris, 7-11,62-66 the amount of patients affected worldwide may be very large. Our results, taken together with other findings in the literature, suggest that the applicability of the DLQI in the management of psoriasis patients may be called into question.…”
Section: Discussionmentioning
confidence: 99%
“…Nemzetközi kutatások korábban felvetették, hogy az életkor, a nem, a diagnózis és kulturális szempontok befolyásolhatják a kérdőíven adott válaszokat, megkérdőjelezték továbbá a kérdőív unidimenzionális voltát, és felhívták a figyelmet arra, hogy a DLQI kevéssé alkalmas a bőrgyógyászati betegségek mentális terhének kifejezésére (20). Hazai, normál populáción és psoriasisos betegek körében végzett kutatások egyaránt diszkrepanciát találtak a DLQI értékek és a hasznosság pontszámok között (21,22).…”
Section: Az éLetminőség Méréseunclassified